Habitual physical activity and social support in adolescents - Gonçalves, Celina (2017)
The support of parents and friends seems central to the involvement of young people in physical activity (PA) (Atkins et al., 2015). The purpose of this study was to analyze the importance of social support on PA levels in adolescents. 864 adolescents of both sexes were included.